2004
DOI: 10.1162/0898929042568550
|View full text |Cite
|
Sign up to set email alerts
|

Reference Frames for Spatial Cognition: Different Brain Areas are Involved in Viewer-, Object-, and Landmark-Centered Judgments About Object Location

Abstract: Functional magnetic resonance imaging was used to compare the neural correlates of three different types of spatial coding, which are implicated in crucial cognitive functions of our everyday life, such as visuomotor coordination and orientation in topographical space. By manipulating the requested spatial reference during a task of relative distance estimation, we directly compared viewer-centered, object-centered, and landmark-centered spatial coding of the same realistic 3-D information. Common activation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

37
218
5
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 278 publications
(268 citation statements)
references
References 85 publications
37
218
5
2
Order By: Relevance
“…This result with regards to distance is in keeping with earlier TMS 18 studies (Lane et al, 2013;Mahayana et al, 2014), and although rFEF has been specifically associated with egocentric processing by some (Grimsen et al, 2008), other studies have demonstrated overlapping activation in such frontal regions between egocentric and allocentric tasks (Chechlacz et al, 2012;Committeri et al,. 2004;Galati et al, 2000;Zaehle et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This result with regards to distance is in keeping with earlier TMS 18 studies (Lane et al, 2013;Mahayana et al, 2014), and although rFEF has been specifically associated with egocentric processing by some (Grimsen et al, 2008), other studies have demonstrated overlapping activation in such frontal regions between egocentric and allocentric tasks (Chechlacz et al, 2012;Committeri et al,. 2004;Galati et al, 2000;Zaehle et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…The role of rPPC in processing near space is in accordance with previous research (Bjoertomt et al, 2002;Halligan & Marshall, 1991;Lane et al, 2013;Mennemeier et al, 1992;Weiss et al, 2000), as is its relationship with egocentric processing (Committeri et al, 2004;Galati et al, 2000;Hillis et al, 2005;Medina et al, 2009;Neggers et al, 2006;Vallar et al, 1999). Neuropsychological research has indicated that the right hemisphere is involved in egocentric processing in near space (Iachini, Ruggiero, Conson & Trojano, 2013), although this finding was based on extensive fronto-parietal lesions in only four patients making it difficult to determine the precise brain area underlying their impairment .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The role of the hippocampus for navigation in large-scale environments has been amply demonstrated in both animal (6-8) and human studies (9-11). Besides the hippocampus, several other areas in the posterior mesial lobe and posterior parietal, occipital, and infero-temporal cortices also play an important role in navigation (9,(12)(13)(14)(15)(16)(17).The neural correlates of navigation in congenital blindness remain elusive, in part owing to the difficulty in testing navigational skills of blind subjects within the setting of a functional brain imaging study. To circumvent this difficulty, we trained blind and sighted subjects in a spatial navigation task using the tongue display unit (TDU), a visual-to-tactile sensory substitution device that converts visual information into electro-tactile pulses applied to the tongue (18, 19).…”
mentioning
confidence: 99%